On the taxonomy of the Italian endemic Hoplia dubia (Rossi, 1792), with the description of two new species (Coleoptera: Scarabaeidae: Melolonthinae) - Uliana, Marco; Liberto, Andrea; Leo, Piero (Zootaxa, 2017)
Hoplia (Hoplia) dubia (Rossi, 1792) (Coleoptera: Scarabaeidae: Melolonthinae: Hopliini) is a species that is endemic of Italy, recorded for scattered localities along the coasts of the peninsula and of Sicily. Following the study of a rather large amount of specimens from the entire known range, Hoplia dubia is herein split into three allopatric species. The true Hoplia dubia is redescribed and a neotype is designated. Two new species, Hoplia (Hoplia) meridiana and Hoplia (Hoplia) messapia, are described and the Hoplia dubia species group is defined. For each species, a full description is given and diagnostic characters are summarized and compared in a table. The three species belonging to the group may be recognized mainly by morphological and chromatic differences in scales, scales density, and by setal pattern, which are all illustrated. Remarks on ecology, ethology, and phenology of adults of the species are also reported. All three species treated in this paper are restricted to coastal sand dunes. The significant loss of this habitat due to anthropogenic pressure raises concern about the conservation status of these species.